KOSAKATA ETNOMEDISIN DALAM PENGOBATAN TRADISIONAL MASYARAKAT DAYAK KANAYATN DIALEK BANYADU - Adir, Leonardus; Patriantoro, Patriantoro; Syahra, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractEthnomedisin vocabulary in traditional medicine of Dayay Kanayatn dialect Banyadu. Traditional medicine tradition in Banyadu society become distinct characteristic of the other Dayak sub-ethnics. Traditional medicine, such as baburas, batido, balenggang and baliatn is considered still sacred and magical that has supernatural powers. Traditional medicine is part of the customs and traditions passed down from generation to generation as a form of traditional medicine is nonmedical. So that traditional medicine is maintained and maintained. This research was conducted in Semade Village, Banyuke Hulu Sub-district, Landak District, which is the residence of Banyadu natives. This study includes the form of lingual units, lexical meanings and cultural meanings, foklor speech, and form of text supplements in the 2013 curriculum education unit. Â Keywords: Â Vocabulary, Etnomedicine, Dayak Traditional Medicine, Kanayatn, Banyadu dialect